2013
DOI: 10.5194/amt-6-3635-2013
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of video disdrometer uncertainties and impacts on estimates of snowfall rate and radar reflectivity

Abstract: Abstract. Estimates of snow microphysical properties obtained by analyzing collections of individual particles are often limited to short timescales and coarse time resolution. Retrievals using disdrometer observations coincident with bulk measurements such as radar reflectivity and snowfall amounts may overcome these limitations; however, retrieval techniques using such observations require uncertainty estimates not only for the bulk measurements themselves, but also for the simulated measurements modeled fro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(66 citation statements)
references
References 31 publications
2
61
0
Order By: Relevance
“…For the short path lengths and observing conditions applicable to these observations, attenuation by gases and snow particles should be negligible [Matrosov, 1998]. Reflectivity for the Rayleigh sphere approximation can then be written as [e.g., Wood et al, 2013] …”
Section: Physical Basismentioning
confidence: 99%
See 3 more Smart Citations
“…For the short path lengths and observing conditions applicable to these observations, attenuation by gases and snow particles should be negligible [Matrosov, 1998]. Reflectivity for the Rayleigh sphere approximation can then be written as [e.g., Wood et al, 2013] …”
Section: Physical Basismentioning
confidence: 99%
“…Disdrometer size distributions, then, are not based on D M but rather on some observed particle size D obs . Wood et al [2013] introduced a parameter to convert observed size distributions into distributions based on D M . Since may vary significantly depending on the disdrometer and snow particle shape, it is added to the state vector to be retrieved, giving…”
Section: The State Vectormentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the CloudSat 2C-SNOW-PROFILE (hereafter, 2C-SNOW), used extensively in this study, provides profiles of instantaneous liquid equivalent surface snowfall rate retrievals based on CloudSat orbital swath data. The 2C-SNOW product uses an optimal estimation procedure to extract snowfall rate from W-band radar reflectivity values, using a priori snow microphysical properties to constrain snowfall rate retrievals [36,37]. It is worth noting that 2C-SNOW surface snowfall rate (and associated SWC profile) is computed only for CPR profiles where the 2C-PRECIP CPR product indicates surface snow probable or certain, or if estimated liquid fraction is <10% (dry snow).…”
Section: Methodology: Gmi-cpr Dataset Descriptionmentioning
confidence: 99%